Determinación de la curvatura Gaussiana en una variedad diferenciable bidimensional compacta - Matute Calderón, Julio César (2018)
In this thesis, we propose a geometric problem in Riemannian, compact and_x000D_ di erentiable manifold with a dimension 2: And we question about the curvature_x000D_ functions that this manifolds admits, and then raised equivalently to the problem in_x000D_ the existence of solution of partial di erential equation, whose solution will depend_x000D_ on the topology of the manifold, that is, the characteristic of Euler